The effects of 12 weeks of high-intensity interval rope skipping training on speed and power indexes in male soccer players - Wei, Bo; Cheng, Wenhu; Qiu, Jiangang (Frontiers in Bioengineering and Biotechnology, 2025)
Research PurposeSpeed ability is an important determinant of a soccer player’s competitive performance in a game, and it also affects the athlete’s sports life and upper limit of competitive level. Power is the core of the soccer player physical ability construction and its influence on the speed of permeate, confrontation, technology, endurance and injury prevention and so on each linThe main objective was to investigate physiological adaptations induced by HIIRS on soccer-specific speed and power qualities of soccer players.Research MethodTwenty-five elite soccer players underwent a 12-week jump rope training program (three 45-min sessions weekly). Participants were randomly assigned to an, EG (n = 13) performing high-intensity intermittent rope skipping (75%–85% HRmax with active intervals at 40%–70% HRmax) and a CG (n = 12) maintaining conventional training (75%–85% HRmax), both monitored via heart rate bands. Pre and post-intervention assessments included: sprint speed (30-m sprint), reaction speed (Optojump 5-s rapid frequency test), visual reaction speed (Optojump visual test), change-of-direction speed (T-test), and explosive power (standing long jump). Data were analyzed via paired samples T-tests.Research ResultsResearch Results. The results of the study found that both high-intensity interval rope skipping (HIIRS) training and traditional training significantly improved sprint speed (HIIRS: P < 0.001; Traditional: P = 0.0009), change of direction speed (HIIRS: P = 0.0103; Traditional:P = 0.0130), and explosive speed (HIIRS:P = 0.0315; Traditional: P = 0.0002). Additionally, HIIRS training significantly improved movement speed (P = 0.0405) and visual reaction speed (P = 0.0441), which were not significantly enhanced by traditional training. Further, HIIRS training demonstrated superior effectiveness compared to traditional training specifically forsprint speed (P = 0.0326) and visual reaction speed (P = 0.0101). This study integrates HIIT principles with rope skipping’s biomechanical SSC action to target neuromuscular adaptations.Research ConclusionThis finding enriches the functionality of the sport of jumping rope and provides an optional training tool for soccer players to develop their speed qualities.